The Shigella kinase effector OspG modulates host ubiquitin signaling to escape septin-cage entrapment - Xian, Wei; Fu, Jiaqi; Zhang, Qinxin; Li, Chuang; Zhao, Yan-Bo; Tang, Zhiheng; Yuan, Yi; Wang, Ying; Zhou, Yan; Brzoic, Peter S.; Zheng, Ning; Ouyang, Songying; et al. (Nature communications, 2024)
Shigella flexneri is a Gram-negative bacterium causing severe bloody dysentery. Its pathogenesis is largely dictated by a plasmid-encoded type III secretion system (T3SS) and its associated effectors. Among these, the effector OspG has been shown to bind to the ubiquitin conjugation machinery (E2~Ub) to activate its kinase activity. However, the cellular targets of OspG remain elusive despite years of extensive efforts. Here we show by unbiased phosphoproteomics that a major target of OspG is CAND1, a regulatory protein controlling the assembly of cullin-RING ubiquitin ligases (CRLs). CAND1 phosphorylation weakens its interaction with cullins, which is expected to impact a large panel of CRL E3s. Indeed, global ubiquitome profiling reveals marked changes in the ubiquitination landscape when OspG is introduced. Notably, OspG promotes ubiquitination of a class of cytoskeletal proteins called septins, thereby inhibiting formation of cage-like structures encircling cytosolic bacteria. Overall, we demonstrate that pathogens have evolved an elaborate strategy to modulate host ubiquitin signaling to evade septin-cage entrapment. Here, Xian et al. use phosphoproteomics to identify that the Shigella effector OspG interacts with a regulator of Cullin-RING ubiquitin ligases to promote the ubiquitination of septins and consequent inhibition of septin cage formation.